Dome-shaped macula: review of the literature - Kal, Magdalena; Winiarczyk, Mateusz; Płatkowska-Adamska, Bernadetta; Walczyk, Anna; Odrobina, Dominik; Mackiewicz, Jerzy (Medical Studies/Studia Medyczne, 2022)
Dome-shaped macula is a pathology of the posterior pole of the eye, characterized by a convex anterior protrusion of the macula. It is most commonly associated with high myopia, but can also occur in non-myopic patients. Patients may report decreased visual acuity but may also be asymptomatic. Due to the lack of specific features in the ophthalmoscopic examination, swept source optical coherence tomography (SS OCT) is the most important diagnostic tool, in which both vertical and horizontal scans should be performed. Despite the lack of effective treatment, patients should be systematically followed up. In some cases, treatment methods such as intravitreal injections of aflibercept, vitrectomy, focal laser photocoagulation and photodynamic therapy are considered.